HAKIKAT KURIKULUM DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Alfiah Hairani; Alliyah Putri; Manna Wassalwa; Nurul Sakinah; Syahrani Yumna Irfani (Universitas 45 Surabaya, 2023)
The curriculum is structured in such a way as to perfect the learning process. The Islamic education curriculum is more emphasized on the concentration of devotion to God, so that in principle it is very closely related to the goals of Islam itself. This paper aims to unravel the nature of the curriculum in the perspective of Islamic educational philosophy itself. This study uses the library study method by collecting data from analyzing sources from related books and journals. Researchers found that the nature of the curriculum in the perspective of Islamic educational philosophy requires various components, namely; the principles of the educational curriculum, the characteristics of the Islamic education curriculum, and the scope of the Islamic education curriculum.